Paediatric Strategy Forum for medicinal product development in mitogen-activated protein kinase pathway inhibitors: ACCELERATE in collaboration with the European Medicines Agency with participation of the Food and Drug Administration. (December 2022) - Pearson, Andrew DJ.; Allen, Carl; Fangusaro, Jason; Hutter, Caroline; Witt, Olaf; Weiner, Susan; Reaman, Gregory; Russo, Mark; Bandopadhayay, Pratiti; Ahsan, Sama; Barone, Amy; Barry, Elly; et al.
Abstract: As the mitogen-activated protein kinase (MAPK) signalling pathway is activated in many paediatric cancers, it is an important therapeutic target. Currently, a range of targeted MAPK pathway inhibitors are being developed in adults. However, MAPK signals through many cascades and feedback loops and perturbing the MAPK pathway may have substantial influence on other pathways as well as normal development. In view of these issues, the ninth Paediatric Strategy Forum focused on MAPK inhibitors. Development of MAPK pathway inhibitors to date has been predominantly driven by adult indications such as malignant melanoma. However, these inhibitors may also target unmet needs in paediatric low-grade gliomas, high-grade gliomas, Langerhans cell histiocytosis, juvenile myelomonocytic leukaemia and several other paediatric conditions. Although MAPK inhibitors have demonstrated activity in paediatric cancer, the response rates and duration of responses needs improvement and better documentation. The rapid development and evaluation of combination approaches, based on a deep understanding of biology, is required to optimise responses and to avoid paradoxical tumour growth and other unintended consequences including severe toxicity. Better inhibitors with higher central nervous systempenetration for primary brain tumours and cancers with a propensity for central nervous system metastases need to be studied to determine if they are more effective than agents currently being used, and the optimum duration of therapy with MAPK inhibition needs to be determined. Systematic and coordinated clinical investigations to inform future treatment strategies with MAPK inhibitors, rather than use outside of clinical trials, are needed to fully assess the risks and benefits of these single agents and combination strategies in both front-line and in the refractory/relapse settings. Platform trials could address the investigation of multiple similar products and combinations. Accelerating the introduction of MAPK inhibitors into front-line paediatric studies is a priority, as is ensuring that these studies generate data appropriate for scientific and regulatory purposes. Early discussions with regulators are crucial, particularly if external controls are considered as randomised control trials in small patient populations can be challenging. Functional end-points specific to the populations in which they are studied, such as visual acuity, motor and neuro psychological function are important, as these outcomes are often more reflective of benefit for lower grade tumours (such as paediatric low-grade glioma and plexiform neurofibroma) and should be included in initial study designs for paediatric low-grade glioma. Early prospective discussions and agreements with regulators are necessary. Long-term follow-up of patients receiving MAPK inhibitors is crucial in view of their prolonged administration and the important involvement of this pathway in normal development. Further rational development, with a detailed understanding of biology of this class of products, is crucial to ensure they provide optimal benefit while minimising toxicity to children and adolescents with cancer. Highlights: Mitogen-activated protein kinase pathway is an important target in glioma, Langerhans cell histiocytosis, neurofibroma and leukaemia Mitogen-activated protein kinase inhibitors can address many unmet needs and have demonstrated activity Combination development and monotherapy optimisation is required New clinical/functional end-points should be agreed prospectively with regulators Inclusion in front-line studies and generating regulatory data are priorities